Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Sure, let's complete the truth table step-by-step.
We need to fill in the column for the inverse of the conditional statement ([tex]\(\sim p \rightarrow \sim q\)[/tex]).
Here is the truth table format that we need to fill in:
\begin{tabular}{|c|c|c|c|}
\hline
p & [tex]$q$[/tex] & [tex]$p \rightarrow q$[/tex] & [tex]$\sim p \rightarrow \sim q$[/tex] \\
\hline
T & T & T & [ ] \\
\hline
T & F & F & [ ] \\
\hline
F & T & T & [ ] \\
\hline
F & F & T & [ ] \\
\hline
\end{tabular}
1. For the case when [tex]\(p\)[/tex] is True (T) and [tex]\(q\)[/tex] is True (T):
- [tex]\(\sim p\)[/tex] (not [tex]\(p\)[/tex]) is False (F) and [tex]\(\sim q\)[/tex] (not [tex]\(q\)[/tex]) is False (F)
- Thus, [tex]\(\sim p \rightarrow \sim q\)[/tex] is True (T)
2. For the case when [tex]\(p\)[/tex] is True (T) and [tex]\(q\)[/tex] is False (F):
- [tex]\(\sim p\)[/tex] (not [tex]\(p\)[/tex]) is False (F) and [tex]\(\sim q\)[/tex] (not [tex]\(q\)[/tex]) is True (T)
- Thus, [tex]\(\sim p \rightarrow \sim q\)[/tex] is True (T)
3. For the case when [tex]\(p\)[/tex] is False (F) and [tex]\(q\)[/tex] is True (T):
- [tex]\(\sim p\)[/tex] (not [tex]\(p\)[/tex]) is True (T) and [tex]\(\sim q\)[/tex] (not [tex]\(q\)[/tex]) is False (F)
- Thus, [tex]\(\sim p \rightarrow \sim q\)[/tex] is False (F)
4. For the case when [tex]\(p\)[/tex] is False (F) and [tex]\(q\)[/tex] is False (F):
- [tex]\(\sim p\)[/tex] (not [tex]\(p\)[/tex]) is True (T) and [tex]\(\sim q\)[/tex] (not [tex]\(q\)[/tex]) is True (T)
- Thus, [tex]\(\sim p \rightarrow \sim q\)[/tex] is True (T)
So, the completed truth table is:
\begin{tabular}{|c|c|c|c|}
\hline
p & [tex]$q$[/tex] & [tex]$p \rightarrow q$[/tex] & [tex]$\sim p \rightarrow \sim q$[/tex] \\
\hline
T & T & T & T \\
\hline
T & F & F & T \\
\hline
F & T & T & F \\
\hline
F & F & T & T \\
\hline
\end{tabular}
Therefore, filling in the blanks we get:
1. For [tex]$p = T$[/tex] and [tex]$q = T$[/tex], [tex]\(\sim p \rightarrow \sim q\)[/tex] = T
2. For [tex]$p = T$[/tex] and [tex]$q = F$[/tex], [tex]\(\sim p \rightarrow \sim q\)[/tex] = T
3. For [tex]$p = F$[/tex] and [tex]$q = T$[/tex], [tex]\(\sim p \rightarrow \sim q\)[/tex] = F
4. For [tex]$p = F$[/tex] and [tex]$q = F$[/tex], [tex]\(\sim p \rightarrow \sim q\)[/tex] = T
We need to fill in the column for the inverse of the conditional statement ([tex]\(\sim p \rightarrow \sim q\)[/tex]).
Here is the truth table format that we need to fill in:
\begin{tabular}{|c|c|c|c|}
\hline
p & [tex]$q$[/tex] & [tex]$p \rightarrow q$[/tex] & [tex]$\sim p \rightarrow \sim q$[/tex] \\
\hline
T & T & T & [ ] \\
\hline
T & F & F & [ ] \\
\hline
F & T & T & [ ] \\
\hline
F & F & T & [ ] \\
\hline
\end{tabular}
1. For the case when [tex]\(p\)[/tex] is True (T) and [tex]\(q\)[/tex] is True (T):
- [tex]\(\sim p\)[/tex] (not [tex]\(p\)[/tex]) is False (F) and [tex]\(\sim q\)[/tex] (not [tex]\(q\)[/tex]) is False (F)
- Thus, [tex]\(\sim p \rightarrow \sim q\)[/tex] is True (T)
2. For the case when [tex]\(p\)[/tex] is True (T) and [tex]\(q\)[/tex] is False (F):
- [tex]\(\sim p\)[/tex] (not [tex]\(p\)[/tex]) is False (F) and [tex]\(\sim q\)[/tex] (not [tex]\(q\)[/tex]) is True (T)
- Thus, [tex]\(\sim p \rightarrow \sim q\)[/tex] is True (T)
3. For the case when [tex]\(p\)[/tex] is False (F) and [tex]\(q\)[/tex] is True (T):
- [tex]\(\sim p\)[/tex] (not [tex]\(p\)[/tex]) is True (T) and [tex]\(\sim q\)[/tex] (not [tex]\(q\)[/tex]) is False (F)
- Thus, [tex]\(\sim p \rightarrow \sim q\)[/tex] is False (F)
4. For the case when [tex]\(p\)[/tex] is False (F) and [tex]\(q\)[/tex] is False (F):
- [tex]\(\sim p\)[/tex] (not [tex]\(p\)[/tex]) is True (T) and [tex]\(\sim q\)[/tex] (not [tex]\(q\)[/tex]) is True (T)
- Thus, [tex]\(\sim p \rightarrow \sim q\)[/tex] is True (T)
So, the completed truth table is:
\begin{tabular}{|c|c|c|c|}
\hline
p & [tex]$q$[/tex] & [tex]$p \rightarrow q$[/tex] & [tex]$\sim p \rightarrow \sim q$[/tex] \\
\hline
T & T & T & T \\
\hline
T & F & F & T \\
\hline
F & T & T & F \\
\hline
F & F & T & T \\
\hline
\end{tabular}
Therefore, filling in the blanks we get:
1. For [tex]$p = T$[/tex] and [tex]$q = T$[/tex], [tex]\(\sim p \rightarrow \sim q\)[/tex] = T
2. For [tex]$p = T$[/tex] and [tex]$q = F$[/tex], [tex]\(\sim p \rightarrow \sim q\)[/tex] = T
3. For [tex]$p = F$[/tex] and [tex]$q = T$[/tex], [tex]\(\sim p \rightarrow \sim q\)[/tex] = F
4. For [tex]$p = F$[/tex] and [tex]$q = F$[/tex], [tex]\(\sim p \rightarrow \sim q\)[/tex] = T
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.